Sensory-Directed Genetic and Biochemical Characterization of Volatile Terpene Production in Kiwifruit. Issue 1 (17th March 2020) - Zeng, Yunliu; Wang, Mindy Y.; Hunter, Denise C.; Matich, Adam J.; McAtee, Peter A.; Knäbel, Mareike; Hamiaux, Cyril; Popowski, Elizabeth A.; Jaeger, Sara R.; Nieuwenhuizen, Niels J.; Yauk, Yar-Khing; Atkinson, Ross G.
Abstract : The signature flavor in ripe kiwifruit is due to the terpene 1, 8-cineole, which is produced via Actinidiachinensis terpene synthase 1b (AcTPS1b). Abstract: Terpene volatiles are found in many important fruit crops, but their relationship to flavor is poorly understood. Here, we demonstrate using sensory descriptive and discriminant analysis that 1, 8-cineole contributes a key floral/eucalyptus note to the aroma of ripe 'Hort16A' kiwifruit ( Actinidia chinensis ). Two quantitative trait loci (QTLs) for 1, 8-cineole production were identified on linkage groups 27 and 29a in a segregating A. chinensis population, with the QTL on LG29a colocating with a complex cluster of putative terpene synthase (TPS)-encoding genes. Transient expression in Nicotiana benthamiana and analysis of recombinant proteins expressed in Escherichia coli showed four genes in the cluster ( AcTPS1a –AcTPS1 d ) encoded functional TPS enzymes, which produced predominantly sabinene, 1, 8-cineole, geraniol, and springene, respectively. The terpene profile produced by AcTPS1b closely resembled the terpenes detected in red-fleshed A . chinensis . AcTPS1b expression correlated with 1, 8-cineole content in developing/ripening fruit and also showed a positive correlation with 1, 8-cineole content in the mapping population, indicating the basis for segregation is an expression QTL. Transient overexpression of AcTPS1b in Actinidia eriantha fruit confirmed this gene produced 1, 8-cineole in Actinidia . Structure-function analysis showed AcTPS1a and AcTPS1b are natural variants at key TPS catalytic site residues previously shown to change enzyme specificity in vitro. Together, our results indicate that AcTPS1b is a key gene for production of the signature flavor terpene 1, 8-cineole in ripe kiwifruit. Using a sensory-directed strategy for compound identification provides a rational approach for applying marker-aided selection to improving flavor in kiwifruit as well as other fruits.